Prerequisites for the establishment and development of financial controlling - S.М. Ratushnyi (Економіка, управління та адміністрування, 2024)
The article is devoted to the identification of historical prerequisites for the formation and development of financial controlling. It was determined that controlling in general and financial controlling, in particular, were studied within the framework of various functional economic sciences (management, control, analysis, accounting and management accounting, etc.), which determines the debate and contradiction of positions regarding its content load and actualizes the need to research historical stages the emergence of financial controlling as an important subsystem of enterprise management and a new business philosophy. The purpose of writing the article is to research the historical prerequisites and stages of the formation of financial controlling based on the assessment of existing world concepts (models) and to determine the peculiarities of its emergence and development in Ukraine. A comparative characterization of the American and German concepts of financial controlling was carried out and their distinguishing features were highlighted: 1) the orientation of the concepts; 2) interpretation of controlling; 3) tasks of controlling; 4) controller’s position at the enterprise; 5) methodological support. The stages of the formation and development of financial controlling are substantiated, which made it possible to distinguish the pre-scientific stage (characterized by the beginning of the formation of the applied foundations of controlling with elements of theory, orientation to the accounting of production costs, the priority of the cost control function and the organization of audit actions in companies) and the scientific stage (related to with the initiation and internationalization of the American and German concepts of controlling, the growing importance of production accounting, the formation of management systems by responsibility centers, the development of controlling methods and tools; the emergence of strategic controlling, the emergence of new areas and objects of controlling). The prerequisites for the formation of domestic concepts of financial controlling are determined (development of market relations, uncertainty of the external environment, need for anti-crisis management methods, internationalization of foreign controlling methods, development of corporate governance, functioning of international professional controlling organizations, transformation of the organization and methodology of information support, the need to introduce the latest information- communication technologies in order to integrate information flows, the development of functional economic sciences and the emergence of new controlling objects), which will contribute to the development of the theoretical foundations of financial controlling. Prospects for further scientific research should be associated with the assessment and clarification of the term «financial controlling» within the existing global and domestic concepts of controlling.